Deviant nicotinic acid adenine dinucleotide phosphate (NAADP)-mediated Ca2+ signaling upon lysosome proliferation. - Dickinson, G; Churchill, G; Brailoiu, E; Patel, S (2010)
Accumulating evidence suggests that the endolysosomal system is a novel intracellular Ca(2+) pool mobilized by the second messenger, nicotinic acid adenine dinucleotide phosphate (NAADP). Although lysosomes in neurons are known to proliferate in numerous neurodegenerative diseases and during the normal course of aging, little is known concerning the effect of lysosomal proliferation on Ca(2+) homeostasis. Here, we induce proliferation of lysosomes in primary cultures of rat hippocampal neurons and PC12 cells through chronic treatment with the cathepsin inhibitor, Z-Phe-Ala-diazomethylketone. We demonstrate that lysosome proliferation increases the size of the lysosomal Ca(2+) pool and enhances Ca(2+) signals in response to direct cellular delivery of NAADP and glutamate, an identified NAADP-producing agonist. Our data suggest that deregulated lysosomal Ca(2+) signaling through NAADP may contribute to neuronal dysfunction and highlight the usefulness of lysosomal hydrolase inhibition in probing NAADP action.